2015
DOI: 10.1007/s13277-015-4067-x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic-antitumor peptide inhibits the migration and invasion of HepG2 cells by an upregulated VGSC β1 subunit

Abstract: Analgesic-antitumor peptide (AGAP), one of the scorpion toxin polypeptides, has been shown to have an antitumor activity. Recombinant AGAP (rAGAP) was shown to affect the migration and invasion of HepG2 cells via a voltage-gated sodium channel (VGSC) β1 subunit. The VGSC β1 subunit was validated as a cell adhesion molecule (CAM) in human hepatocellular carcinoma (HCC) cell lines. rAGAP suppresses the migration and invasion of HepG2 cells but has no significant effect of human liver HL7702 cells without β1 subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Studies have reported that BmK AGAP inhibited proliferation, migration and induced apoptosis in SW480 and SHG-44 cancer cells (40, 44). It was also reported that the analgesic peptide inhibited the migration and invasion of HepG2 cells (45). In the present study, we employed MCF-7, a differentiated breast cancer cell line that express estrogen receptor, and MDA-MB-231, a poorly differentiated triple- negative breast cancer cell line, as models and found that the scorpion analgesic peptide BmK AGAP, could effectively inhibit breast cancer cell stemness and epithelial-mesenchymal transition both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have reported that BmK AGAP inhibited proliferation, migration and induced apoptosis in SW480 and SHG-44 cancer cells (40, 44). It was also reported that the analgesic peptide inhibited the migration and invasion of HepG2 cells (45). In the present study, we employed MCF-7, a differentiated breast cancer cell line that express estrogen receptor, and MDA-MB-231, a poorly differentiated triple- negative breast cancer cell line, as models and found that the scorpion analgesic peptide BmK AGAP, could effectively inhibit breast cancer cell stemness and epithelial-mesenchymal transition both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 97%
“…Zhao et al reported that BmK AGAP inhibits Nav 1.5 in SHG-14 cells and down-regulates p-AKT, pp-38, p-Erk1/2, and p-c-Jun, which gradually decreased the expression of NF-κB (40). Guo et al also reported that the analgesic peptide up-regulated the VGSC β1 subunit to inhibit migration and invasion of HepG2 cells (45). In this present study, the role of rBmK AGAP on the expression of Nav 1.5, PTX3, and TNF-α as well as NF-κB signal transduction, were further investigated to illustrate the potential molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported some physiological effects of the Chinese scorpion BmK venom known for its antiepileptic, analgesic, and, recently, antitumor properties. The use of this Chinese scorpion BmK venom revealed apoptogenic, immunosuppressive, and antiproliferative properties and demonstrated the potential of the cocktail for cancer-related diseases (Zhao et al, 2011; Li et al, 2014; Al-Asmari et al, 2016, 2018; Guo et al, 2016; Liu et al, 2017). The antitumor effect of the BmK venom was later accredited to an analgesic peptide called BmK AGAP and others (Zhao et al, 2011; Guo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…VGSCs are aberrantly expressed in tumors and play an important role in tumor growth and metastasis . β1 subunit has been reported in carcinoma cell lines derived from breast cancer , cervical cancer , and hepatocellular carcinoma , and it has a role in tumor growth and metastasis. β2 in prostate cancer cells increases adhesion, process outgrowth, migration, and invasion .…”
Section: Discussionmentioning
confidence: 99%